The Association between Enterprise Risk Management and Corporate Governance Quality: The Mediating Role of Internal Audit Performance - MUSTAFA, Fairouz Mohammed; AL-NIMER, Munther (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).27, 2018)
The purpose of this study is to evaluate the association of enterprise risk management and quality of corporate governance. In this aspect, the internal audit performance has been analyzed as the mediating force in organizations. The problem of this study identified from the fact that corporate governance in Jordan is diagnosed with symptoms of health hazards in areas of laws. Yet, enterprise systems proved its benefits. Therefore, the aim of this research is to examine this association. The population covers all firm listed on Amman stock exchange, the sample consists of 168 firms, they have been chosen based on the existence of risk management system. The respondents are risk management specialists and internal auditors. Structural equation model is used for the statistical analysis. The results reveal a direct positive relationship between enterprise risk management and corporate governance quality. It also reveals a partial mediating effect of the internal audit performance, since the relationships become more justified. The findings highlight that organizations require implementing different practice for effectively allocating resources in adopting enterprise risk management. It also emphasized on that the firms should take into consideration human factors of usability before the adoption. Beside, it is considered as a first international study examine the relations in this frame.